2022
DOI: 10.1186/s12872-022-02721-7
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning to predict post-operative acute kidney injury stage 3 after heart transplantation

Abstract: Background Acute kidney injury (AKI) stage 3, one of the most severe complications in patients with heart transplantation (HT), is associated with substantial morbidity and mortality. We aimed to develop a machine learning (ML) model to predict post-transplant AKI stage 3 based on preoperative and perioperative features. Methods Data from 107 consecutive HT recipients in the provincial center between 2018 and 2020 were included for analysis. Logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…AI applications also affect clinician outcomes, specifically, clinician decision making, clinician workflow and efficiency, and clinician evaluations and acceptance of AI applications. In this review, thirty-two studies reported clinician outcomes of AI in cardiac surgery (4,5,7,8,10,11,1338).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AI applications also affect clinician outcomes, specifically, clinician decision making, clinician workflow and efficiency, and clinician evaluations and acceptance of AI applications. In this review, thirty-two studies reported clinician outcomes of AI in cardiac surgery (4,5,7,8,10,11,1338).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies discussed clinician efficiency (5,10,11,16,18,20,2224,29,36,37). Machine learning was used to predict survival after heart transplantation allowing better patient selection and reducing organ wastage (18,37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Multivariate logistic regression 30,31,36,43,48,54,55,60,62,65,67,69,75,76,78,80,95,106,107,110 (2) Previously validated scores such as perioperative medicine-related scores (e.g., ASA status, POSSUM, Charlson Comorbidity Index, or National Surgical Quality Improvement Program calculator scores) 30,32,49,61,100,104 or other scores 58,62 (e.g., Bariclot tool, STOP-BANG score, Mallampati test, various frailty indexes, and the acute kidney injury score) 34,49,58,72,79,82,86,114,121 (3) Clinical assessment 42,52,88 Overall, the machine learning models described in these articles outperformed their technical or clinical comparator, with an average increase in AUC and accuracy between 0.2-0.3, except for that of Chen et al 38 where the ASA score alone, despite a lower AUC, had higher accuracy compared to neural network and logistic regression models.…”
Section: Benchmarksmentioning
confidence: 99%
“…In recent years, machine-learning algorithms have been widely used as a data-driven modeling method in many fields, such as geotechnical engineering [ 27 ], traffic safety [ 28 ], material engineering [ 29 ], and biomedicine [ 30 ]. To improve computational accuracy and computational efficiency, Breima proposed the random forest (RF) algorithm in 2001 [ 31 ].…”
Section: Introductionmentioning
confidence: 99%